2018
DOI: 10.1111/jphp.12908
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel cyclopropyl derivatives as subtype-selective ligands for estrogen receptor

Abstract: Although these cyclopropyl derivatives showed lower binding affinities on ERs compared to 17β-estradiol, five of these compounds exhibited binding to ERα only and therefore might serve as a promising lead compound for further development of novel subtype-selective SERMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In same year, Wang et al assessed cyclopropyl derivatives to develop ERα selective novel SERMs with the aid of docking using Discovery Studio 2.5 against both ERα (pdb entry 1A52) and ERβ(pdb entry 3OLS) [230,233]. The authors were able to discover five compounds with ERα activity (IC 50 ranging between 1.79-6.27 µM) but with non-detectable binding to ERβ using FP assays [233]. Luciferase reporter Assay confirmed that all the molecules were antagonistic towards ERα and were antiproferative in MCF-7 cells [233].…”
Section: Only Active At High Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In same year, Wang et al assessed cyclopropyl derivatives to develop ERα selective novel SERMs with the aid of docking using Discovery Studio 2.5 against both ERα (pdb entry 1A52) and ERβ(pdb entry 3OLS) [230,233]. The authors were able to discover five compounds with ERα activity (IC 50 ranging between 1.79-6.27 µM) but with non-detectable binding to ERβ using FP assays [233]. Luciferase reporter Assay confirmed that all the molecules were antagonistic towards ERα and were antiproferative in MCF-7 cells [233].…”
Section: Only Active At High Concentrationsmentioning
confidence: 99%
“…The authors were able to discover five compounds with ERα activity (IC 50 ranging between 1.79-6.27 µM) but with non-detectable binding to ERβ using FP assays [233]. Luciferase reporter Assay confirmed that all the molecules were antagonistic towards ERα and were antiproferative in MCF-7 cells [233]. In a similar study, Jin and group used AutoDock Vina4.0 to dock Benzofuran derivatives in an attempt to identify novel SERMs using the pdb entry 3ERT as the target protein for docking [54,234].…”
Section: Only Active At High Concentrationsmentioning
confidence: 99%